Late Miocene pollen record and quantitative paleoclimate and paleoelevation reconstructions for the Jianzha Basin, northeastern Tibetan Plateau - Beibei Zhang; Chaofeng Fu; Feng Wang; Fengyan Lu; Chen Liang; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Millennial cold–dry events during marine isotope stage 11a based on sedimentary records from the Heqing Basin and their global climatic dynamical responses - Guohui Liu; Xinwen Xu; Shenghui Wang; Lirong Hou; Yuqing Zhang; Liu Yang; Jingfang Zhang; Yuzhu Zhang; Hui Zhao; Chaofeng Fu; Xiaoke Qiang; Wen Liu; et al. (Global and Planetary Change, 2026)

Rapid isolation of indigenous degraders combined with autochthonous bioaugmentation for in situ remediation of groundwater contaminated with complex organic pollutants: a pilot-scale study - Zefan Liu; Qianbin Pan; Yulong Fu; Jiawen Yang; Hao Leng; Chaofeng Shen (Biodegradation, 2026)

The application of cold-adapted microorganisms in biphenyl biodegradation: Responses and mechanisms to environmental temperature fluctuations - Zefan Liu; Jinou Huang; Wei Li; Yangyang Jia; Yulong Fu; Chaofeng Shen (Journal of Environmental Sciences, 2026)

Different coercivity magnetic components in a lacustrine sequence from Heqing Basin and its linkage with millennial Indian summer monsoon variability since 52 ka - Lirong Hou; Xinwen Xu; Xiaoke Qiang; Qiongqiong Wang; Hui Zhao; Chaofeng Fu; Guohui Liu; Shenghui Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Complete and sequential reductive dechlorination of 1,2-dichloroethane and 1,2-dichloropropane by a Trichlorobacter-dominated consortium - Zhenghua Wu; Jixing Wan; Zijiao Zhang; Junao Jin; Hao Leng; Yulong Fu; Chaofeng Shen (Journal of Environmental Sciences, 2026)

The surface nutrients in China's coastal waters in the winter of 2025 - Chaofeng Wang; Jiaxuan Ni; Xiaoyu Wang; Longwen Fu; Lilian Wen; Zhen Guo; Long Gao; Xinhua Chen; Jun Ma (Marine Environmental Research, 2025)

Supplementation of exogenous RpfE facilitates polychlorinated biphenyl degradation in soil by stimulating endogenous rpfE expression and promoting cell growth - Hong Zou; Fengjun Xu; Xinyi Li; Yangyang Jia; Yulong Fu; Chaofeng Shen (Journal of Hazardous Materials, 2025)

Magnetic proxy in the Heqing drill core revealed Indian Summer Monsoon variations linked with AMOC at the orbital -scale during the late Pleistocene - Xinwen Xu; Xiaoke Qiang; Xubin Li; Haijun Qiu; Hui Zhao; Chaofeng Fu; Ziyi Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Palaeoenvironmental evolution of the Northeastern Tibetan Plateau and its response to global temperature change during the Late Miocene: Geochemical and clay mineralogical evidence from the Jianzha Basin - Peng Jia; Chaofeng Fu; Yougui Song; Jinhua Du; Jun Zuo; Saimaiti Akemu; Beibei Zhang (Global and Planetary Change, 2025)

PJ-YOLO: Prior-Knowledge and Joint-Feature-Extraction Based YOLO for Infrared Ship Detection - Yongjie Liu; Chaofeng Li; Guanghua Fu (Journal of Marine Science and Engineering, 2025)
Infrared ship images have low resolution and limited recognizable features, especially for small targets, leading to low accuracy and poor generalization of traditional detection methods. To address this, we design a prior knowledge auxiliary loss for leveraging the unique brightness distribution of infrared ship images, we construct a joint feature extraction module that sufficiently captures context awareness, channel differentiation, and global information, and then we propose a prior-knowledge- and joint-feature-extraction-based YOLO (PJ-YOLO) for use in detecting infrared ships. Additionally, a residual deformable attention module is designed to integrate multi-scale information, enhancing detail capture. Experimental results on the SFISD and InfiRray Ships datasets demonstrate that the proposed PJ-YOLO achieves state-of-the-art detection performance for infrared ship targets. In particular, PJ-YOLO achieves improvements of 1.6%, 5.0%, and 2.8% in mAP50, mAP75, and mAP50:95 on the SFISD dataset, respectively.

Copper single-atom catalysts for broad-spectrum antibiotic-resistant bacteria (ARBs) antimicrobial: Activation of peroxides and mechanism of ARBs inactivation - Zhihao Lin; Yulong Fu; Bingni Zhang; Feiyu Wang; Chaofeng Shen (Journal of Hazardous Materials, 2024)

The risk of viable but non-culturable (VBNC) enterococci and antibiotic resistance transmission during simulated municipal sludge composting - Bingni Zhang; Yulong Fu; Feiyu Wang; Pingri Jin; Pengcheng Xu; Haoming Li; Xiaojie Xu; Chaofeng Shen (Waste Management, 2024)

Composition, diel dynamic and biotic-abiotic interaction of marine neustonic zooplankton in the oligotrophic South China Sea - Chaofeng Wang; Zhimeng Xu; Li Zhao; Jun Ma; Yuan Zhao; Zhen Guo; Qingjing Fu; Wuchang Zhang (Marine Environmental Research, 2024)

Drying-wetting cycle enhances stress resistance of Escherichia coli O157:H7 in a model soil - Jing Se; Yinan Xie; Qingxu Ma; Lin Zhu; Yulong Fu; Xin Xu; Chaofeng Shen; Paolo Nannipieri (Environmental Pollution, 2024)

Paleoclimatic application of spectral parameters to the eolian red clay of the Jianzha Basin, northeastern margin of the Tibetan Plateau - Chaofeng Fu; Ju’e Tian; Xinwen Xu; Yougui Song; Jun Zuo; Feng Wang; Lin Chen; Pengfei Li; Xiaoke Qiang (Science China Earth Sciences, 2024)

Magnetostratigraphy and relative paleointensity study of a late Quaternary lacustrine sediment sequence from Southwest China and its chronological significance - Xinwen Xu; Xiaoke Qiang; Ziyi Yang; Hui Zhao; Chaofeng Fu; Qiongqiong Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

First Asian fossil record of Platydictya (Amblystegiaceae) from the lower Miocene and its paleoenvironmental significance - Liyan Guo; Liang Xiao; Ya Li; Xiangchuan Li; Qin Leng; Nan Sun; Junfeng Guo; Chaofeng Fu; Jianan Wang; Deshuang Ji (Frontiers of Earth Science, 2023)

FgBUD14 is important for ascosporogenesis and involves both stage‐specific alternative splicing and RNA editing during sexual reproduction - Jie Liang; Xianhui Fu; Chaofeng Hao; Zhuyun Bian; Huiquan Liu; Jin‐Rong Xu; Guanghui Wang (Environmental Microbiology, 2021)
Summary In wheat head blight fungus Fusarium graminearum , A‐to‐I RNA editing occurs specifically during sexual reproduction. Among the genes with premature stop codons (PSCs) that require RNA editing to encode full‐length proteins, FgBUD14 also had alternative splicing events in perithecia. In this study, we characterized the functions of FgBUD14 and its post‐transcriptional modifications during sexual reproduction. The Fgbud14 deletion mutant was slightly reduced in growth, conidiation and virulence. Although deletion of FgBUD14 had no effect on perithecium morphology, the Fgbud14 mutant was defective in crozier formation and ascus development. The FgBud14‐GFP localized to the apex of ascogenous hyphae and croziers, which may be related to its functions during early sexual development. During vegetative growth and asexual reproduction, FgBud14‐GFP localized to hyphal tips and both ends of conidia. Furthermore, mutations blocking the splicing of intron 2 that has the PSC site had no effect on the function of FgBUD14 during sexual reproduction but caused a similar defect in growth with Fgbud14 mutant. Expression of the non‐editable FgBUD14 Intron2‐TAA mutant allele also failed to complement the Fgbud14 mutant. Taken together, FgBUD14 plays important roles in ascus development, and both alternative splicing and RNA editing occur specifically to its transcripts during sexual reproduction in F . graminearum .

Proteomic changes of viable but nonculturable (VBNC) Escherichia coli O157:H7 induced by low moisture in an artificial soil - Jing Se; Yulong Fu; Yinan Xie; Fengjun Xu; Chaofeng Shen; Paolo Nannipieri (Biology and Fertility of Soils, 2021)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)